PENGGUNAAN MEDIA BERBASIS TEKS CERITA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA - Nur Rohman; Zulhannan; Koder; Asti Fauziah (STKIP Subang, 2025)
This study aims to describe the implementation of maharah kalam (Arabic speaking skills) instruction based on narrative texts and to examine its impact on students’ speaking ability and responses in Grade VII of SMP IT Al-FARABI. The research employed a qualitative descriptive approach. Data were collected through classroom observations, semi-structured interviews, and documentation. The research subjects consisted of one Arabic language teacher and Grade VII students who participated in maharah kalam learning activities using narrative text media. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation.The findings indicate that the use of narrative text media is effective in improving students’ maharah kalam abilities. Improvements were observed in several aspects of speaking skills, including fluency, pronunciation, vocabulary mastery, intonation, and self-confidence. Vocabulary mastery and self-confidence showed the most significant improvement, while pronunciation and intonation improved at a moderate to high level. Furthermore, both teachers and students expressed positive responses toward the use of narrative texts, as this medium made the learning process more communicative, engaging, and encouraged students to be more active in speaking Arabic. Overall, narrative text media can serve as an effective alternative instructional strategy to enhance Arabic speaking skills at the junior high school level.